6-Benzylaminopurine treatment maintains the quality of Chinese chive (Allium tuberosum Rottler ex Spreng.) by enhancing antioxidant enzyme activity - Li-e JIA; Sheng LIU; Xiao-ming DUAN; Chao ZHANG; Zhan-hui WU; Ming-chi LIU; Shao-gui GUO; Jin-hua ZUO; Li-bin WANG (Journal of Integrative Agriculture, 2017)
Chinese chive usually develops an off-flavor after a short storage time. To explore effective ways to maintain the postharvest quality of Chinese chive, the effect of exogenous application of 6-benzylaminopurine (6-BA) on postharvest quality and antioxidant activity of chive was evaluated, and the mechanism of the physiological responses of chive to 6-BA treatment was explored. Chives were sprayed for 10 min with 100, 300, or 500 mg L−1 6-BA or with alkaline solution as the control, then stored at (2±1)°C with a relative humidity (RH) of 80–85%. We found that 300 mg L−1 6-BA significantly delayed yellowing and chlorophyll degradation, maintained the total phenolic and flavonoid content, and improved the activities of antioxidant enzymes, including superoxide dismutase (SOD), catalase (CAT) and peroxidase (POD). In conclusion, we identified exogenous application of 6-BA as an effective method for maintaining postharvest quality of Chinese chive. In addition, our finding that the activities of antioxidant enzymes increase in response to exogenous 6-BA provides new insights into the mechanism of cytokinin-based postharvest fresh-keeping.